(untitled) (Research, Society and Development, 2023)
The present research deals with the family agroindustry as one of the pillars that favor the strengthening of family agriculture, addressing, in particular, the difficulties faced by the family farmer with regard to the process of regularization of the agroindustries and the types of legal entities in which these producers can become involved. frame. The work also points out some of the requirements required by national legislation with regard to the regularization process of family agroindustries. The general objective of the research was to analyze the legal requirements for the regulation of the family agroindustry, pointing out the legal requirements for the regularization of the family agroindustries and also identifying the types of legal entities that the agroindustries can fit according to each individual situation. To achieve the proposed objectives, the research used a narrative-type bibliographic review, where data were collected through the analysis of articles, dissertations and theses (full text), published on the platforms of CAPES, SCIELO, BDTDs, IBGE, FUNASA, SENAR, CONAB, CAIXA etc; as well as on e-Journals sites and on Google Academic; the search criterion was based on the use of keywords directly and indirectly correlated with the study, with a time span of the last five years, except for the use of classic works. As a result, it was observed that there are several benefits that the regularization of the family agroindustry brings to family farmers, on the other hand, due to complex processes and obstacles to achieving this regularization, many family farmers choose to remain informal.